Proses Penanganan Ship to Ship (STS) Transfer LNG Valencia Knutsen dengan LNG Asia Axcellence pada PT. Batam Mitra Suplindo - Fernando Jose Sumbayak; Suratni Ginting; Meriah Kita Deliana (Jurnal Transformasi Bisnis Digital, 2025)
PT. Batam Mitra Suplindo is a company engaged in ship agency services. The ship agency service process at PT. Batam Mitra Suplindo starts from the initial arrival of the ship, loading and unloading activities, until the ship departs to the next destination port. Ship to Ship (STS) transfer is a method of transferring cargo between ships that requires careful coordination and supervision, especially in handling Liquified Natural Gas (LNG) cargo, which is volatile and high-risk. As one of the ship agency companies in the Batam waters area, PT. Batam Mitra Suplindo plays an important role in supporting the smooth process of Ship to Ship (STS) Liquified Natural Gas (LNG). This paper aims to comprehensively examine the Ship to Ship (STS) Liquified Natural Gas (LNG) handling process carried out by PT. Batam Mitra Suplindo, covering the planning stage, coordination with related institutions, technical implementation, and post-transfer evaluation. The research method used is field research, observation, and library research. The research results show that the success of Ship to Ship (STS) Liquified Natural Gas (LNG) highly depends on compliance with standard operating procedures (SOP), readiness of licensing documents, and synergy with the Port Health Office, Harbour Master, and ship operators.